Analisis Harga Pokok Produksi dan Penjualan pada UMKM Boembu Rumah Catering - Abdullah Ariq Akbar; Dehan Akramann; Erland Ahmad Daniyal; Yuni Astuti Tri Tartiani (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to analyze the calculation of Cost of Goods Manufactured (COGS) and sales strategies at MSME Boembu Rumah Catering. Using a direct interview method with the business owner, this research explores the components of production costs which include raw materials, labor, and overhead costs. The results showed that Boembu Rumah Catering was able to determine a competitive and efficient selling price, thus achieving a profit of 98%. In conclusion, accurate COGS calculation and proper understanding of cost components can improve the efficiency and profitability of MSME businesses, while strengthening competitiveness in the catering market.